Companies' performance and behaviour responding to crisis during Covid-19 pandemic: a case study of the Czech Republic - Ekaterina Chytilová; Milan Talíř (Entrepreneurship and Sustainability Issues, 2024)
The aim of the paper is to find out whether the behaviour of B2B and B2C enterprises differed in the pandemic period in terms of disruption, the extent of measures taken and the financial situation in the following period. To achieve the main objective, a questionnaire survey was conducted in Czech companies with a predominantly B2B or B2C business relationship. Two research questions were defined, which were answered by testing a total of 6 hypotheses. The parametric two-sample one-factor ANOVA and Pearson's Chi-squared test were used to test the hypotheses. The test results suggest that the correlation between the number of operation barriers and the level of disruption is more pronounced for B2C than for B2B. B2C businesses were more likely to use tools such as simplifying organisational structure or changing product offerings to combat the impact of pandemic. In contrast, B2B businesses used tools such as working from home and moving online to a greater extent. The correlation between the level of disruption and the use of remedial measures is only valid for the B2B group. The link between the measures taken and the economic situation after the pandemic was confirmed for both B2B and B2C businesses (to a greater extent). The survey results are valid only for B2B or B2C businesses in the Czech Republic. The results are limited to these measures only, other measures were considered irrelevant for the purpose of the study. The results are limited to the crisis period; results may differ in other periods.